2015
DOI: 10.1016/j.actpsy.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The oculomotor resonance effect in spatial–numerical mapping

Abstract: We investigated automatic Spatial-Numerical Association of Response Codes (SNARC) effect in auditory number processing. Two experiments continually measured spatial characteristics of ocular drift at central fixation during and after auditory number presentation. Consistent with the notion of a spatially oriented mental number line, we found spontaneous magnitude-dependent gaze adjustments, both with and without a concurrent saccadic task. This fixation adjustment (1) had a small-number/left-lateralized bias a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
2
15
1
Order By: Relevance
“…The fact that the ORE was induced by unpredictive cues underlines the obligatory nature of the number-induced attentional shifts in visual space (see for similar results Hartmann et al, 2015a ; Ranzini et al, 2016 ; Yu et al, 2015 ). The associated pattern had a leftward/small-number bias similar to the findings reported before (Cai & Li, 2015 ; Foulsham, Gray, Nasiopoulos, & Kingstone, 2013 ; Loetscher, Bockisch, & Brugger, 2008 ; Myachykov et al, 2015 ), which may be a sign of “pseudoneglect” resulting from the attentional preference for small numbers, or a reflection of the selective use of odd numbers as stimuli (e.g. Nuerk et al, 2005 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The fact that the ORE was induced by unpredictive cues underlines the obligatory nature of the number-induced attentional shifts in visual space (see for similar results Hartmann et al, 2015a ; Ranzini et al, 2016 ; Yu et al, 2015 ). The associated pattern had a leftward/small-number bias similar to the findings reported before (Cai & Li, 2015 ; Foulsham, Gray, Nasiopoulos, & Kingstone, 2013 ; Loetscher, Bockisch, & Brugger, 2008 ; Myachykov et al, 2015 ), which may be a sign of “pseudoneglect” resulting from the attentional preference for small numbers, or a reflection of the selective use of odd numbers as stimuli (e.g. Nuerk et al, 2005 ).…”
Section: Discussionsupporting
confidence: 84%
“…Ristic et al, 2006 ; Casarotti et al, 2007 ); it occurs as soon as minimal semantic information is available. One recent study using a similar paradigm Myachykov, Cangelosi, Ellis, & Fischer ( 2015 ) also reported a bi-phasic distribution of the drift-related ORE effect with early (~400 ms) and late (~800 ms) peaks. Also, a similar early signature of sensorimotor activation from conceptual processing was previously reported by means of an ERPs analysis showing that shifts of attention induced by numerical magnitude arise immediately after semantic magnitude processing (Ranzini, Dehaene, Piazza, & Hubbard, 2009 ).…”
Section: Discussionmentioning
confidence: 85%
“…There were clear effects at a latency of ~1,600 s, and small, brief, effects at ~800 ms. Importantly, the subjects in Experiments 2–4 of the current study, on average, responded much earlier than the substantial effects from eye position reported in 73 (Experiment 2: 545 ± 28 ms; Experiment 3: 639 ± 28 ms; Experiment 4: 762 ± 24 ms). In addition, work using a psychophysical method similar to Experiment 2 in this study found no consistent eye-position bias in a left/right judgment task with reference to the subjects’ subjective straight ahead (Experiment 1B in Lewald, 1997 74 ).…”
Section: Discussionmentioning
confidence: 44%
“…Any eye position effects in the current study would only be a source of additional error if they were unrelated to number magnitude. However, a recent study showed a tendency for eye movements to the left after subjects heard small numbers, and movements to the right for larger numbers (experiment 2 in 73 ). There were clear effects at a latency of ~1,600 s, and small, brief, effects at ~800 ms.…”
Section: Discussionmentioning
confidence: 94%
“…In magnitude comparison (e.g., indicating the numerically larger number of two presented numbers) or parity judgment (e.g., indicating whether a given number is odd or even) tasks, participants are faster at giving left hand responses to small numbers and right hand responses to large numbers (Dehaene, Bossini, & Giraux, 1993). Moreover, numerous eye-tracking studies have documented the impact of this horizontal spatial-numerical mapping on eye movements, which typically accompany shifts of visual attention (Fischer, Warlop, Hill, & Fias, 2004;Moeller, Fischer, Nuerk, & Willmes, 2009;Myachykov, Cangelosi, Ellis, & Fischer, 2015;Myachykov, Ellis, Cangelosi, & Fischer, 2016;Schwarz & Keus, 2004).…”
Section: Introductionmentioning
confidence: 99%